PENERAPAN MODEL PEMBELAJARAN PROBLEM SOLVING DENGAN APLIKASI GOOGLE MEET UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN LKS DALAM PEMBELAJARAN OPERASI HITUNG BILANGAN BULAT PADA SISWA KELAS VII H SMP NEGERI 3 ABIANSEMAL TAHUN PELAJARAN 2020/2021 - Ni Nyoman Suastini (Widyadari : Jurnal Pendidikan, 2021)
Student Worksheet (LKS) is one of the tools where students can carry out the learning process by reading alone, following examples related to learning, doing tasks according to the subject matter. The purpose of this study was to determine whether there was a student's response and to improve students' ability to answer arithmetic operations on integers in class VII H SMP Negeri 3 Abiansemal by applying the problem solving learning model through the google meet application. This type of research is classroom action research. This research was conducted in VII H of SMP Negeri 3 Abiansemal. The subjects of the action research were students of class VII H of SMP Negeri 3 Abiansemal in the 2020/2021 school year, and the object of this research was a study of understanding integer arithmetic operations and student responses to problem solving learning models. In this study, two cycles were used and each cycle went through four stages of the activity process which included (1) planning, (2) action, (3) observation, and (4) evaluation and reflection. Data collection techniques using test and observation methods. Collecting data using observation techniques for qualitative data. The results of the action research are (1) the application of the problem solving learning model with the google meet application can improve the ability to answer integer arithmetic operations (2) There is a positive response from students in the ability to answer integer arithmetic operations in class VII H students of SMP Negeri 3 Abiansemal,